1864 - Menschen zwischen den Mächten. 1864 - Mennesker mellem magterne - Hering, Rainer; Schultz Hansen, Hans; Imberger, Elke (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2016)
The German-Danish War of 1864 has been extensively investigated in the literature -as far as the major political and military events are concerned. The civilian population, the civil administration and the national movements during the war, as well as the economic consequences and the formation of identities after the war, have been more or less neglected. In order to change this, German and Danish historians have written this book. It is the result of a German-Danish conference organized by the the federal state archives in Schleswig and Aabenraa.